2010
DOI: 10.1111/j.1469-0691.2009.02910.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Mediterranean spotted fever in Greece

Abstract: Forty-five days after the first confirmed and fatal Crimean-Congo haemorrhagic fever (CCHF) case in Greece in 2008, a female patient with similar signs and symptoms (high fever, thrombocytopaenia) and resident of the same area, was admitted to the University General Hospital of Alexandroupolis. Before admission, she had visited a local hospital where a cephalosporin was prescribed. A rash manifested over subsequent days, which was misdiagnosed as an allergy to the drug. Upon admission to the University Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
1
17
0
3
Order By: Relevance
“…Recently, the mortality rate in Portugal reached 13% (9/71) of patients with MSF, including many patients with confusion and obtundation (67%), and a multivariate analysis revealed the following independent predictors associated with fatal outcome: hyperbilirubinemia, acute renal failure, and the absence of rash (226). Other fatal cases were reported in France, Greece, Bulgaria, and Turkey (213,229,240,247). Rickettsia conorii subsp.…”
Section: Tick-borne Rickettsiae In Europe Species Identified As Pathomentioning
confidence: 99%
“…Recently, the mortality rate in Portugal reached 13% (9/71) of patients with MSF, including many patients with confusion and obtundation (67%), and a multivariate analysis revealed the following independent predictors associated with fatal outcome: hyperbilirubinemia, acute renal failure, and the absence of rash (226). Other fatal cases were reported in France, Greece, Bulgaria, and Turkey (213,229,240,247). Rickettsia conorii subsp.…”
Section: Tick-borne Rickettsiae In Europe Species Identified As Pathomentioning
confidence: 99%
“…In a previous study using two target genes (17-kDa antigen gene and ompA gene) in a clinical sample both PCRs were positive (R. conorii). 7 The fact that R. conorii was not detected in the present study is likely due to its pathogenicity for ticks, since it was shown that exposure of Rh. sanguineus to R. conorii strain Malish produces lasting harmful effects on their survival.…”
Section: Limitations Of the Studymentioning
confidence: 58%
“…2 Four tick-borne Rickettsiae have been currently identified in humans in Greece: R. conorii, R. aeschlimannii, R. sibirica mongolotimonae and R. slovaca, while R. massiliae and R. rhipicephali were identified only in ticks. [3][4][5][6][7][8][9] Unusual increased tick aggressiveness was observed in summer 2008 in northeastern Greece resulting in increased number of persons bitten by ticks, and two fatal cases, one caused by R. conorii and one by Crimean-Congo hemorrhagic fever virus (the first and only report in Greece). 7,10 As a result, many residents of the region sought medical advice in the emergency departments of the regional hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine typhus is generally underdiagnosed in childhood (5). Although there are reports on infections caused by R. conorii (13,14), there is not any study on murine typhus from northern Greece. A seroprevalence study conducted in 2000 in various prefectures of northern Greece showed that IgG antibodies against R. conorii and R. typhi were detected in 1% and 2% of the population in Kavala prefecture, respectively (15).…”
Section: Case Reportmentioning
confidence: 99%